The role of learning styles and strategies in English language proficiency achievement by the EFL learners (intermediate level) / K Kalai Mathi A/P Kernagaran - K Kalai Mathi, Kernagaran (2014)
English is known as the language of International communication and it is the most important language worldwide. Thus, English language proficiency has become very important in order to fulfil the requirements of higher learning Institutions as well as in corporate field around the globe. Mastering English helps a person to have job prospects and increase their standard of living. Most people find it a tremendous task to acquire English as their second or foreign language. It does require a lot of effort to understand and use language in an appropriate way in order to be an expert or good user. So, this study aims to examine the role of learning styles and strategies used in English language proficiency achievement by the EFL learners at the (Intermediate Level). Firstly, this research attempts to find out the most preferred language learning styles and strategies by the participants based on the results obtained from Learning Style Inventory (LSI) and Strategy Inventory for Language Learning (SILL) questionnaires adapted from Oxford (1990). Secondly, this research tries to identify the impact of the learning styles and strategies used in proficiency achievement mainly in Listening and Reading skills. Lastly, this research explores other factors that influence students’ proficiency achievement with reference to the data obtained from the participants’ ethnographic information. 18 Intermediate Level students; 9 males and 9 females from English for Speakers of Other Languages (ESOL) class were selected randomly for this study as respondents. Data was collected through the respondents’ biographical background and using two questionnaires of Language Learning Style Inventory (LLSI) consisting of 24 items with Often, Sometimes and Seldom answers to describe the learners as Visual, Auditory or Tactile. The questionnaire on Strategy Inventory for Language Learning (SILL) consists of 50 statements divided into six parts in five- point Likert-scale responses. Therefore IELTS Listening and IELTS Reading tests were conducted to obtain the band score of the participants to assess their proficiency level. The results achieved show that, the most preferred language learning style is the Auditory followed by Visual. Therefore cognitive, metacognitive and memory strategies are the most preferred language learning strategies by the respondents. The selection of items in the questionnaires do reflect on the band scores obtained from the IELTS Listening and IELTS Reading Tests. It proves that there is a relationship between language learning styles and strategies with proficiency achievement. It was found that age, gender and curiosity relate to their proficiency achievements especially in the reading skill.